The Effectiveness Test of Oil Phase Ointment Containing Snakehead Fish (Channa striata) Extract on Open Stage II Acute Wounded Wistar Strain Male Rats - Fransisca Daisa; Mohamad Andrie; Wintari Taurina (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
The snakehead (Channa striata) contained fatty acids omega-3 and omega-6 are useful as nutrients in accelerating the wound healing process. This study aims to determine the effectiveness of the oil phase extract ointment snakehead in the healing of acute wounds open stage II. Testing the effectiveness of wound healing using 6 groups: normal, gel bioplacenton (positive control), ointment base (negative control), ointments snakehead extract oil phase concentration of 10; 20 and 40% of the 4 rats with acute wounds open stage II and observation until day 16 injury. The area of the wound was measured with the image J program Macbiophotonic, calculated% healing power, and AUC values. A statistical test to the total AUC values per rat with SPSS for Windows 22.0 program using One Way ANOVA and Post-hoc LSD test. The results showed a significant difference in the negative group with ointment concentration of 20% (p <0.05). The treatment group phase ointment fish oil extract is effective for wound healing is best to have a concentration of 20% for percentage of wound healing power of 97.157% and the average AUC value of 865.683% of the day.